PREVALÊNCIA DE ANTICORPOS ANTI-Toxocara spp. EM CRIANÇAS ATENDIDAS EM DOIS SISTEMAS DE SAÚDE E FATORES DE RISCO ASSOCIADOS À TOXOCARÍASE, NO MUNICÍPIO DE PRESIDENTE PRUDENTE, SÃO PAULO - Leli, Flávia Noris Chagas (2009)
Toxocariasis has been considered one of the most important helminthozoonosis worldwide. The purpose of this study was to evaluate the seroprevalence of anti-Toxocara antibodies and the risk and protective factors for toxocariasis in 252 children from two different socioeconomic classes. The seroprevalences of Toxocara infection in 126 children who received care from private health services (middle-class) and 126 children who received care from public health services (disadvantaged children) were 9.5% and 12.7%, respectively. The risk factors (RF) of toxocariasis were evaluated using bivariate analysis complemented by logistic regression. Toxocara seroprevalence was inversely proportional to family income. Being a female and belonging to a family whose monthly income was higher were considered protective factors. However, owning a cat was a RF for children from both the total population and each of the subgroups, whereas owning a dog was considered a RF for only the middle-class children. This study shows that epidemiological risk and protective factors of toxocariasis can influence distinctively different strata of a population. Thus, it is relevant to evaluate the risk and protective factors for different socioeconomic classes to design future investigations and programs to prevent the human infection of Toxocara spp. and other geohelminths.